Autophagy-mediated NKG2D internalization impairs NK cell function and exacerbates radiation pneumonitis - Wang, Ruiqing; Ma, Xinyue; Zhang, Xinyu; Jiang, Dizhi; Mao, Hongyuan; Li, Zerun; Tian, Yu; Cheng, Bo (Frontiers in Immunology, 2023)
Introduction Radiation pneumonitis is a critical complication that constrains the use of radiation therapy for thoracic malignancies, leading to substantial morbidity via respiratory distress and lung function impairment. The role of Natural killer (NK) cells in inflammatory diseases is well-documented; however, their involvement in radiation pneumonitis is not fully understood. Methods To explore the involvement of NK cells in radiation pneumonitis, we analyzed tissue samples for NK cell presence and function. The study utilized immunofluorescence staining, western blotting, and immunoprecipitation to investigate CXCL10 and ROS levels, autophagy activity, and NKG2D receptor dynamics in NK cells derived from patients and animal models subjected to radiation. Result In this study, we observed an augmented infiltration of NK cells in tissues affected by radiation pneumonitis, although their function was markedly diminished. In animal models, enhancing NK cell activity appeared to decelerate the disease progression. Concomitant with the disease course, there was a notable upsurge in CXCL10 and ROS levels. CXCL10 was found to facilitate NK cell migration through CXCR3 receptor activation. Furthermore, evidence of excessive autophagy in patient NK cells was linked to ROS accumulation, as indicated by immunofluorescence and Western blot analyses. The association between the NKG2D receptor and its adaptor proteins (AP2 subunits AP2A1 and AP2M1), LC3, and lysosomes was intensified after radiation exposure, as demonstrated by immunoprecipitation. This interaction led to NKG2D receptor endocytosis and subsequent lysosomal degradation. Conclusion Our findings delineate a mechanism by which radiation-induced lung injury may suppress NK cell function through an autophagy-dependent pathway. The dysregulation observed suggests potential therapeutic targets; hence, modulating autophagy and enhancing NK cell activity could represent novel strategies for mitigating radiation pneumonitis.